Decadal changes in the Sea of Marmara indicate degraded ecosystem conditions and unsustainable fisheries - Akoglu, Ekin; Saygu, İsmet; Demirel, Nazli (Frontiers in Marine Science, 2024)
Globally, all marine ecosystems are under pressure by anthropogenic stressors. However, semi-enclosed seas are at a greater risk of degradation due to their limited connectivity to open seas. This leads to a greater accumulation of pollutants and abrupt regime shifts triggered by unsustainable exploitation of living resources, as ecosystems exhibit low degrees of redundancy and more frequent large-scale episodic events such as harmful algal blooms. The Sea of Marmara is a semi-enclosed marine region that has been subjected to various anthropogenic stressors since the 1990s. Recently, local and governmental authorities have employed basin-wide ecosystem management plans to control and manage point and nonpoint (diffuse) sources of pollutants. However, the management of fisheries in relation to the dynamics of the Sea of Marmara food web has attracted less attention from policymakers, even though fisheries exploitation is one of the most significant anthropogenic pressures. In this study, we capitalized on a previous static ecosystem model of the Sea of Marmara by revising and extending it to simulate the changes between 1990 and 2020. We delineated the temporal dynamics and regime shifts in the food web in terms of ecosystem structure and function by using ecological indicators and developed quantitative management advice for its fisheries. The results showed that the ecosystem has experienced three regimes since 1990, with regime shifts occurring with the onset of the 2000s and the mid 2010s. The first regime exhibited high diversity and material cycling, the second regime was characterized by low diversity and increased impact of fisheries, and the third regime culminated in a fished-down food web state. The analysis of fishery dynamics showed that the majority of harvested species were overexploited. We suggest that the implementation of quotas for exploited species should be considered an immediate solution to the unsustainable exploitation of fish stocks and can help restore ecosystem conditions.